The issue of objectivity and subjectivity in social research – Analytical sociological study – - Alkasem, Mayada Mustafa (Journal of Humanities & Social Sciences, 2021)
The aim of the research is to clarify the issue of subjectivity and objectivity in social research, and to what extent it is possible to achieve objectivity and distance from subjectivity as much as possible in social research, where the concept of subjectivity and objectivity was defined, and the views of some sociologists on this issue, as well as the call to reconcile them, also came this study To clarify the role of quantitative (objective) and qualitative (subjective) systematic integration in achieving accuracy and objectivity in the study of social phenomena, as we relied on the analytical sociological approach as an approach to analysis in the field of social studies, and the study reached the need to achieve objectivity and establish unity between objectivity and subjectivity in any study Social, as the study confirmed that objectivity is really a relative issue that cannot be achieved far from subjectivity in social research, as there is no objective science completely independent of any value perspective, and that the systematic integration between subjectivity and objectivity contributes to reaching accuracy in social research. The research also emphasized a set of recommendations, the most important of which are: the call to achieve subjectivity and objectivity and not to abolish subjectivity in the study of social phenomena, and to call researchers in the social sciences to achieve systematic integration between them.